DETERMINASI POLITIK PADA PROSES PEMBENTUKAN DAN PENEGAKAN HUKUM DI INDONESIA - Rahman, Abdul (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2020)
This article outlines the relationship between politics and law in the formation and enforcement of the law in Indonesia until the current reform era. There are three models of relations in describing legal and political relations. First, as Das Sein, the political determinant of the law because the law was born from the political process so that the law is a crystallization of competing for political desires. Secondly, as Das Sollen, the Law of determinants on the politics of every political agenda should be subject to the rules of the law. Thirdly, politics and laws influence each other because political lawlessness will be wronged while the law without an escort will be paralyzed. In the process of forming legislation by political institutions, the role of political power is very decisive because political institutions are formally given the authority in making the law. Political institutions that are not given such authority will become a vacuum. Here it appears that political institutions are only a tool of the group of political power holders. There are three main elements directly related to law enforcement efforts. First, the element of artificial lawn is a legislative institution. Second, the element of law enforcement is the police, prosecutors, and judges. Third, environmental elements include personal citizens and society.Keywords: Determination, politic, formation, and enforcement of the law.